Answer:
p
Step-by-step explanation:
The value of h depends on the values of p.
So h is the dependent variable and p is the independent one
Answer:
Step-by-step explanation:
Hope this helped!
<h3>~AH1807</h3><h3>Peace!</h3>
Answer:
Step-by-step explanation:
The recursive rule tells you the initial term of the sequence is a1 = -3, and the common difference is d=7. (7 is the value added to one term to get the next term.)
Putting these values into the formula for the explicit rule gives ...
an = a1 +d(n -1)
an = -3 + 7(n -1)
let the number of
Total number of people : adults + children
Total money earned from adults :
Total money earned from children :
Therefore, total money = money earned from each Adult and children.
Now, let's plug the value of x from equation [1] into equation [2]
let's plug the value of y in equation [1]
Hence, we get :
Correct option is C
_____________________________
Answer:
Step-by-step explanation:
Evaluate 6(5-(6-5)-3) = 6(5-1-3) {first solve innermost bracket}
= 6* (5-4) = 6*1 =6